First whole genome sequencing of Escherichia coli carrying mcr-1 from pig in Argentina - Pellegrini, Juan Leandro (2024)
The objective of this study is to communicate the findings of the first whole genome sequencing of a colistin-resistant Escherichia coli isolate harboring mcr-1 gene obtained from a pig in Argentina. Genomic DNA was sequenced using the MinION Oxford Nanopore platform. The libraries were prepared using a SQK-RBK110-96 protocol. The sequencing process was conducted on a MinION Mk1C MIN 101-C, utilizing a FLO-MIN106 flow cell. The quality of the reads was evaluated using NanoPlot. De novo assembly was conducted using Canu 1.6 and the quality of contigs was evaluated using QUAST. Annotation was performed using Prokka. The CBC20 strain exhibited a colistin MIC of 4 μg/mL. The genome size was 5178653 bp with a GC content of 50,31%. The N50 value was 133,250, while the L50 value was 21.A total of 11,620 genes, 11,518 coding sequences, 77 transfer RNAs and 24ribosomal RNAs were identified. A serotype O9:H37 with sequence type ST-297 was observed. A total of seven antimicrobial resistance genes were identified, including mcr-1.5, blaTEM-1B, blaEC-18, blaTEM-70, aph(3´)-Ia, mph(A) and sul3. The presence of punctual mutations was observed in the genes encoding the proteins GyrA (S83L, D87N) and ParC (S80I). Five distinct plasmid replicon types were identified, including IncFII, IncY, IncFIB, IncX1 and Col440II. Our findings may assist in the comprehension of the mechanisms of antimicrobial resistance, genomic epidemiology and dissemination of mcr-1 gene among animals and environment, which could potentially impact human health.